World Englishes. - Hopkins, Tometro 1943-; Decker, Ken 1955-; McKenny, John (London, UK Bloomsbury Academic, 2017)
World Englishes is a series presenting a comprehensive, detailed survey of English as it is spoken all over the world.
v. 1. The British Isles / edited by Tometro Hopkins and John McKenny -- v. 2. North America / edited by Tometro Hopkins -- v. 3. Central America / edited by Tometro Hopkins and Ken Decker.
Includes bibliographical references and index.
Keywords: English language -- Foreign countries; English language -- Study and teaching -- Foreign speakers; English language -- Variation; Intercultural communication